Strained Bedfellows: Pagans, New Agers, and “Starchy Humanists” in Unitarian Universalism - Lee, Richard Wayne (Sociology of religion, 1995)
Despite the considerable resistance of its largely humanist membership, Unitarian Universalism in recent years assimilated such new religious movements as neopaganism and new age. In accounting for this apparently unlikely development, I examine the historical development of Unitarian Universalism, its integration of new religious movements, and the internal conflict this provoked. I identify three factors that, in combination, make sociological sense of the significant impact on Unitarian Universalism of these movements.